The effect of economic sanctions on the volume of trade in the agriculture sector of Iran and business partners in the EU - Seyed Yaghoub Zeraatkish; Zahra Farahmand (Universitas Islam Indonesia, 2019)
Iranian economy was under pressured during the period of international trade sanctions. This paper investigates the effect of the economic sanctions on the bilateral agriculture trade of Iran with ten main trading partners in European Union between 2001 to 2015. A modified gravity model is used as an empirical international trading model and panel data are used for investigating the effect of sanctions. Findings/Originality: In the absence of sanction, the effect of all independent variables, except for population, is as expected by the theory. Under the sanction the effect of GDP and population is lower than those of without sanction. The effect of foreign exchange fluctuation gets more intense during the sanction due to instability of financial sector. Distance, however, is not a significant variable to explain the bilateral trade both in the absence and under the sanction. The weak sanction period lowered the bilateral trade by 7.5 percent lower, but unexpectedly it was 12 percent higher during the strong sanction period.